The Role and Significance of Non-invasive Methods, with a Particular Focus on Shear Wave Elastography in Hepatic Fibrosis Staging - Hasani Jusufi, Arzana; Trajkovska, Meri; Popova-Jovanovska, Rozalinda; Calovska-Ivanova, Viktorija; Ramadani, Atip; Andreevski, Vladimir (Open Access Macedonian Journal of Medical Sciences, 2022)
Shear Wave Elastography (SWE) represents a new, non-invasive method, used in the diagnosis of diffuse liver diseases. The method has been widely used instead of liver biopsy - an invasive procedure with potential major risk complications. Compared to liver biopsy, SWE provides an examination of larger areas of the liver, thus providing better staging of hepatic fibrosis. 30 patients were included in the study on basis of previous clinical, biochemical, and ultrasound findings indicating a presence of a chronic liver lesion. Patients were divided into three groups: 6 patients with steatosis, 13 patients with viral hepatitis, and 11 patients with liver cirrhosis. Liver damage biochemical markers, serum markers of liver fibrosis, and SWE were determined in all patients. Statistical analysis revealed a positive correlation between SWE results, and the values of biochemical markers of the hepatic lesion, as well as serum markers of liver fibrosis.